Abatacept in the treatment of adult dermatomyositis and polymyositis: a randomised, phase IIb treatment delayed-start trial. Issue 1 (9th October 2017) - Tjärnlund, Anna; Tang, Quan; Wick, Cecilia; Dastmalchi, Maryam; Mann, Herman; Tomasová Studýnková, Jana; Chura, Radka; Gullick, Nicola J; Salerno, Rosaria; Rönnelid, Johan; Alexanderson, Helene; Lindroos, Eva; et al.
Abstract : Objectives: To study the effects of abatacept on disease activity and on muscle biopsy features of adult patients with dermatomyositis (DM) or polymyositis (PM). Methods: Twenty patients with DM (n=9) or PM (n=11) with refractory disease were enrolled in a randomised treatment delayed-start trial to receive either immediate active treatment with intravenous abatacept or a 3 month delayed-start. The primary endpoint was number of responders, defined by the International Myositis Assessment and Clinical Studies Group definition of improvement (DOI), after 6 months of treatment. Secondary endpoints included number of responders in the early treatment arm compared with the delayed treatment arm at 3 months. Repeated muscle biopsies were investigated for cellular markers and cytokines. Results: 8/19 patients included in the analyses achieved the DOI at 6 months. At 3 months of study, five (50%) patients were responders after active treatment but only one (11%) patient in the delayed treatment arm. Eight adverse events (AEs) were regarded as related to the drug, four mild and four moderate, and three serious AEs, none related to the drug. There was a significant increase in regulatory T cells (Tregs), whereas other markers were unchanged in repeated muscle biopsies. Conclusions: In this pilot study, treatment of patients with DM and PM with abatacept resulted in lower disease activity in nearly half of the patients. In patients with repeat muscle biopsies, an increased frequency of Foxp3 + Tregs suggests a positive effect of treatment in muscle tissue.